Genotype-Dependent Effects of Dalcetrapib on Cholesterol Efflux and Inflammation: Concordance With Clinical Outcomes. (August 2016) - Tardif, Jean-Claude; Rhainds, David; Brodeur, Mathieu; Feroz Zada, Yassamin; Fouodjio, René; Provost, Sylvie; Boulé, Marie; Alem, Sonia; Grégoire, Jean C.; L'Allier, Philippe L.; Ibrahim, Reda; Guertin, Marie-Claude; et al.
Abstract : Background—: Dalcetrapib effects on cardiovascular outcomes are determined by adenylate cyclase 9 gene polymorphisms. Our aim was to determine whether these clinical end point results are also associated with changes in reverse cholesterol transport and inflammation. Methods and Results—: Participants of the dal-OUTCOMES and dal-PLAQUE-2 trials were randomly assigned to receive dalcetrapib or placebo in addition to standard care. High-sensitivity C-reactive protein was measured at baseline and at end of study in 5243 patients from dal-OUTCOMES also genotyped for the rs1967309 polymorphism in adenylate cyclase 9. Cholesterol efflux capacity of high-density lipoproteins from J774 macrophages after cAMP stimulation was determined at baseline and 12 months in 171 genotyped patients from dal-PLAQUE-2. Treatment with dalcetrapib resulted in placebo-adjusted geometric mean percent increases in high-sensitivity C-reactive protein from baseline to end of trial of 18.1% ( P =0.0009) and 18.7% ( P =0.00001) in participants with the GG and AG genotypes, respectively, but the change was −1.0% ( P =0.89) in those with the protective AA genotype. There was an interaction between the treatment arm and the genotype groups ( P =0.02). Although the mean change in cholesterol efflux was similar among study arms in patients with GG genotype (mean: 7.8% and 7.4%), increases were 22.3% and 3.5% with dalcetrapib and placebo for those with AA genotype ( P =0.005). There was a significant genetic effect for change in efflux for dalcetrapib ( P =0.02), but not with placebo. Conclusions—: Genotype-dependent effects on C-reactive protein and cholesterol efflux are supportive of dalcetrapib benefits on atherosclerotic cardiovascular outcomes in patients with the AA genotype at polymorphism rs1967309. Clinical Trials Registration—: ClinicalTrials.gov; Unique Identifiers: NCT00658515 and NCT01059682. Abstract : Supplemental Digital Content is available in the text.